An aluminum matrix composite material, its preparation method and application

By adding micron-scale SiC particles and carbon nanotubes to the aluminum alloy matrix, combined with ball milling and strong shear stirring casting technology, a high-density aluminum-based composite material was prepared, which solved the problem of insufficient wear resistance at high temperatures and achieved stable use in high temperature environments.

CN120041714BActive Publication Date: 2025-07-11LOUDI WENCHANG TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510518653.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2025-07-11
Estimated Expiration
2045-04-24

AI Technical Summary

Technical Problem

The existing aluminum-based composite materials have insufficient wear resistance at high temperatures and are difficult to apply to parts that are under high temperature reciprocating friction for a long time.

Method used

By adding a hybrid reinforced phase of micron-scale SiC particles and carbon nanotubes to the aluminum alloy matrix, combined with ball milling technology and strong shear stirring casting technology, a high-density aluminum-based composite material is prepared, and the element ratio is optimized to improve the high-temperature performance of the material.

Benefits of technology

It significantly improves the elastic modulus, wear resistance and high-temperature tensile properties of the material, maintains a stable coefficient of friction, and is suitable for long-term high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120041714B_ABST
    Figure CN120041714B_ABST
Patent Text Reader

Abstract

The present application provides an aluminum matrix composite material, a preparation method and an application thereof, which are composed of the following components in mass percentages: Si 4.0% - 10%, Cu 1.5% - 6.5%, Mg 0.3% - 1.0%, Ag 0.1% - 0.6%, Mn 0.02% - 0.3%, Ti 0.02% - 0.5%, Zr 0.01% - 0.2%, micron-sized SiC particles 5% - 30%, carbon nanotubes 0.1% - 3%, and the balance is Al. The CNTs-SiCp hybrid reinforced aluminum matrix composite material prepared by the present application has high density, high modulus, high wear resistance, excellent tensile properties at room temperature and high temperature, and good thermal exposure stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of aluminum alloys, and particularly relates to an aluminum matrix composite material, a preparation method thereof, and an application thereof. Background Art

[0002] The wear-resistant aluminum matrix composite material is a composite material composed of an aluminum alloy matrix and high wear-resistant materials (such as silicon carbide - SiC, alumina - Al2O3, etc.). The main components in the composite material are the Al alloy matrix, reinforcing phases such as Al2O3 and SiC. These materials all have ultra-light characteristics, which can significantly reduce the weight of the support structure, reduce the infrastructure construction cost, and are also convenient for transportation and construction. Secondly, the addition of ceramic particles significantly improves the wear resistance of the component.

[0003] In the related art, a multi-scale particle-reinforced wear-resistant aluminum matrix composite material with low density and uniform dispersion of reinforcing particles was prepared by ball milling + powder metallurgy technology. In the related art, an SiC particle-reinforced aluminum matrix composite material was prepared based on an Al-Si-Cu series alloy. This composite material still maintains a high hardness at 200°C, but as the temperature continues to rise, the material properties will decay rapidly, and it is difficult to be applied to parts in a high-temperature reciprocating friction working condition for a long time. Summary of the Invention

[0004] This application is made in view of the above problems, and its purpose is to provide an aluminum matrix composite material with excellent high-temperature wear resistance.

[0005] Specifically, the first aspect of this application provides an aluminum matrix composite material, which is composed of the following components in mass percentages:

[0006] Si 4.0% - 10%, Cu 1.5% - 6.5%, Mg 0.3% - 1.0%, Ag 0.1% - 0.6%, Mn 0.02% - 0.3%, Ti 0.02% - 0.5%, Zr 0.01% - 0.2%, micron-sized SiC particles 5% - 30%, carbon nanotubes 0.1% - 3%, and the balance is Al.

[0007] According to one technical solution in the technical solution of the aluminum matrix composite material of this application, it has at least the following beneficial effects:

[0008] Through a large number of studies and industrial practices, it has been found that simply adding a single SiC particle reinforcement to cast aluminum alloy does not significantly refine the matrix structure. Grains are prone to grow during long-term high-temperature exposure, making it difficult to obtain stable high-temperature resistance performance. In the early stage of this application, the composition range and the ratio of each element in the aluminum alloy matrix material were finely optimized and designed to ensure excellent performance matching. Through the reasonable design of the ratio of micron-sized SiC particles to nano-sized CNTs (carbon nanotubes), the aluminum matrix composite material not only significantly improves the elastic modulus and wear resistance but also maintains a good match of high room temperature (25°C) strength and thermal fatigue performance.

[0009] On the other hand, this application solves the problems that are prone to occur during the preparation of the SiCp / Al composite material with a single reinforcing phase, such as uneven distribution of SiC particles, weak interfacial bonding, and high porosity. By introducing a hybrid CNT reinforcing phase, this application significantly refines the matrix structure. During the solidification process, CNTs are distributed at the α-Al grain boundaries to inhibit their growth, significantly improving the pushing effect of grains on the micron-sized reinforcing phase SiCp and regulating the dispersion distribution of the reinforcing phase in the composite material.

[0010] The CNTs-SiCp hybrid reinforced aluminum matrix composite material prepared in this application has high density, excellent mechanical properties, high wear resistance, high-temperature tensile properties, and good microstructural properties after long-term thermal exposure.

[0011] According to some embodiments of this application, the particle size of the micron-sized SiC particles is 3μm to 15μm.

[0012] According to some embodiments of this application, the particle size of the micron-sized SiC particles is 5μm to 15μm.

[0013] According to some embodiments of this application, the aspect ratio of the carbon nanotubes is 50 to 200:1.

[0014] According to some embodiments of this application, the mass fraction of the micron-sized SiC particles is 10% to 30%.

[0015] According to some embodiments of this application, the mass fraction of the carbon nanotubes is 0.3% to 2%.

[0016] The increase in the content of SiCp can significantly improve the hardness, modulus, and wear resistance of the material; the increase in CNTs can significantly refine the grains, avoid the pushing phenomenon of the matrix grains on SiCp that is prone to occur during the solidification of the single SiCp / Al composite material, and at the same time, due to the self-lubricity of CNTs, the wear resistance of the SiCp / Al material can be further improved.

[0017] According to some embodiments of this application, the hardness of the aluminum matrix composite material is above 180 HBw.

[0018] According to some embodiments of the present application, the compressive strength of the aluminum matrix composite material is above 180 MPa at 300 °C.

[0019] According to some embodiments of the present application, the compressive strength of the aluminum matrix composite material is above 450 MPa at 25 °C.

[0020] The second aspect of the present application provides a method for preparing an aluminum matrix composite material, comprising the following steps:

[0021] Pre-oxidize the SiC particles to obtain pre-oxidized SiC particles;

[0022] Ball-mill aluminum powder and carbon nanotubes to obtain a carbon nanotube / Al precursor;

[0023] Mix the molten metal, pre-oxidized SiC particles and carbon nanotube / Al precursor and then perform suction casting. After the suction casting is completed, perform heat treatment to obtain the aluminum matrix composite material;

[0024] The aluminum matrix composite material is composed of the following components by mass percentage:

[0025] Si 4.0% - 10%, Cu 1.5% - 6.5%, Mg 0.3% - 1.0%, Ag 0.1% - 0.6%, Mn 0.02% - 0.3%, Ti 0.02% - 0.5%, Zr 0.01% - 0.2%, micron-sized SiC particles 10% - 30%, carbon nanotubes 0.3% - 3%, and the balance is Al.

[0026] Through pre-oxidation treatment, a layer of SiO2 is formed on the surface of SiCp, further improving the wettability with the matrix alloy.

[0027] According to some embodiments of the present application, the temperature of the pre-oxidation treatment is 800 °C - 1200 °C.

[0028] According to some embodiments of the present application, the time of the pre-oxidation treatment is 3 h - 8 h.

[0029] According to some embodiments of the present application, the particle size of the micron-sized SiC particles is 5 μm - 15 μm.

[0030] According to some embodiments of the present application, the atmosphere of the pre-oxidation treatment is an oxygen atmosphere.

[0031] According to some embodiments of the present application, the mass ratio of the aluminum powder to the carbon nanotubes is 10 - 20:1.

[0032] According to some embodiments of the present application, the ball-to-material ratio of the ball milling is 1:4 - 8.

[0033] According to some embodiments of the present application, the ball milling time is 1 h to 4 h.

[0034] According to some embodiments of the present application, after melting the metal element source in the aluminum matrix composite material, it is refined to obtain a metal melt.

[0035] According to some embodiments of the present application, the melting temperature is 610 °C to 700 °C.

[0036] According to some embodiments of the present application, after melting, it is kept warm for 5 min to 10 min.

[0037] According to some embodiments of the present application, the mixing temperature is 600 °C to 650 °C.

[0038] According to some embodiments of the present application, the mixing time is 15 min to 30 min.

[0039] According to some embodiments of the present application, before suction casting, vacuum strong shear stirring is applied in the semi-solid range.

[0040] According to some embodiments of the present application, the suction casting is vacuum suction casting.

[0041] According to some embodiments of the present application, the temperature of the suction casting is 20 °C to 50 °C above the liquidus.

[0042] According to some embodiments of the present application, the heat treatment includes solution treatment, quenching and aging treatment.

[0043] According to some embodiments of the present application, the temperature of the solution treatment is 500 °C to 530 °C.

[0044] According to some embodiments of the present application, the time of the solution treatment is 2 h to 10 h.

[0045] According to some embodiments of the present application, the aging treatment temperature is 180 °C to 220 °C.

[0046] According to some embodiments of the present application, the time of the aging treatment is 6 h to 15 h.

[0047] According to some embodiments of the present application, natural aging heat treatment can also be carried out after the aging treatment. According to some embodiments of the present application, the time of the natural aging heat treatment is 30 h to 400 h.

[0048] According to some embodiments of the present application, the method for preparing the aluminum matrix composite material includes the following steps:

[0049] S1. Raw material preparation:

[0050] SiC pre-oxidation treatment:

[0051] The micron-sized SiC particles are heat-treated at a high temperature of 800 - 1200 °C for 3 - 8 h in an oxygen atmosphere to obtain pre-oxidized SiC particles;

[0052] Prepare the CNTs / Al precursor:

[0053] After pickling and passivating the CNTs, passivated CNTs are obtained;

[0054] The passivated CNTs and aluminum powder are mixed and ball-milled at a mass ratio of 1:10 - 20 to obtain the CNTs / Al precursor;

[0055] Prepare the molten metal:

[0056] The metal raw materials are configured according to the mass percentage content of each metal element component, and after mixing the metal raw materials, they are heated to 610 °C - 700 °C and held for 5 min - 10 min to obtain the matrix alloy melt;

[0057] The slag on the matrix alloy melt is skimmed off, a refining agent is added, the melt is stirred for 3 - 10 min, and slagging is carried out to obtain the refined molten metal;

[0058] S2. Prepare the composite material melt:

[0059] After mixing the pre-oxidized SiC particles, the CNTs / Al precursor and the refined molten metal, the temperature of the melt is lowered to 600 °C - 650 °C, and the melt is mechanically stirred in a semi-solid state for 15 min - 30 min to obtain the CNTs-SiCp / Al composite material melt;

[0060] S3. Vacuum suction casting:

[0061] The CNTs-SiCp / Al composite material melt is heated to 20 °C - 50 °C above the liquidus line, and the vacuum suction casting technology is adopted. The melt is suction-cast into shape under the pressure difference formed by the inert gas and the vacuum. A cooling water channel is provided inside the suction-casting mold, and an aluminum matrix composite casting is obtained under the effect of rapid cooling;

[0062] S4. Heat treatment:

[0063] The aluminum matrix composite casting is processed to obtain the aluminum matrix composite material.

[0064] The preparation method of this application creatively combines the ball-milling process with the strong shear stirring casting technology; this method includes the following steps:

[0065] ①. Design the composition of the cast aluminum alloy matrix;

[0066] ②. High-temperature pre-oxidation treatment of SiC particles;

[0067] ③. Prepare the CNTs / Al precursor by ball milling;

[0068] ④. Semi-solid vacuum strong shear stirring and mixing to refine the molten metal, pre-oxidized SiC particles and the CNTs / Al precursor;

[0069] ⑤. Vacuum suction casting.

[0070] The preparation cost of this application is low, and near-net shaping of large-sized composite material components can be realized. The aluminum matrix composite material prepared by this method has excellent properties such as low density, high elastic modulus, low residual stress, high wear resistance and excellent thermal exposure performance.

[0071] In the cross-section of the CNTs / Al precursor powder after ball milling in this application, the CNTs are embedded in the aluminum powder, achieving sufficient dispersion.

[0072] The third aspect of this application provides the application of the aluminum matrix composite material described in the first aspect of this application and / or the aluminum matrix composite material prepared by the preparation method described in the second aspect of this application in the preparation of high-temperature wear-resistant parts.

[0073] The hardness of the aluminum matrix composite material of this application can reach above 180 HBw, and the tensile strength remains above 180 Mpa under high-temperature service at 300 °C. It combines the high wear resistance of SiCp / Al composites and the self-lubricity of CNTs, and can maintain a stable friction coefficient.

[0074] The aluminum matrix composite material of this application can be used in parts that are in a high-temperature reciprocating friction working condition for a long time, such as the braking system of new energy vehicles, and has a significant effect of reducing the unsprung weight.

[0075] According to some embodiments of this application, the wear-resistant part includes a vehicle braking system.

[0076] According to some embodiments of this application, the vehicle braking system includes a new energy vehicle braking system. Description of the Drawings

[0077] In order to more clearly illustrate the technical solutions in the embodiments of the drawings or the prior art, the following will briefly introduce the drawings required to be used in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the drawings. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on the structures shown in these drawings.

[0078] Figure 1 It is the microstructural diagram of the CNTs-SiCp hybrid reinforced aluminum matrix composite material under transmission electron microscopy in Example 1.

[0079] Figure 2Microstructure diagram of the CNTs-SiCp hybrid reinforced aluminum matrix composite for Example 1.

[0080] Figure 3 Microstructure diagram of the CNTs-SiCp hybrid reinforced aluminum matrix composite for Example 2.

[0081] Figure 4 Wear scar result diagram of the CNTs-SiCp hybrid reinforced aluminum matrix composite for Example 2.

[0082] The realization, functional features and advantages of this drawing will be further described with reference to the embodiments and the drawings. Detailed implementation manners

[0083] In order to make the objectives, technical solutions and advantages of this application clearer, the following describes and explains this application in combination with embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit this application. Based on the embodiments provided in this application, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of this application.

[0084] Obviously, the following description is only some examples or embodiments of this application. For those of ordinary skill in the art, this application can also be applied to other similar scenarios without creative efforts. In addition, it can also be understood that although the efforts made in this development process may be complex and lengthy, for those of ordinary skill in the art related to the content disclosed in this application, some designs, manufacturing or production changes based on the technical content disclosed in this application are only conventional technical means and should not be understood as the content disclosed in this application being insufficient.

[0085] If there is no special indication, the "including" and "comprising" mentioned in this application mean open-ended or closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or only the components listed can be included or comprised.

[0086] If there is no special indication, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) while B is true (or exists); or both A and B are true (or exist).

[0087] Example 1

[0088] This embodiment is an aluminum matrix composite composed of a matrix alloy and a reinforcing phase.

[0089] In this embodiment, the aluminum matrix composite material is composed of the following components by mass percentage:

[0090] Si 6.5%, Cu 3.5%, Mg 0.35%, Ag 0.2%, Mn 0.3%, Ti 0.1%, Zr 0.1%, SiC particles (10 μm) 12%, carbon nanotubes 0.5% and the balance Al.

[0091] The preparation method of the aluminum matrix composite material in this embodiment consists of the following steps:

[0092] S1. Raw material preparation:

[0093] High-temperature pre-oxidation treatment of SiC particles:

[0094] The SiC particles (D50 is 10 μm) are oxidized at 1100 °C in an oxygen atmosphere for 4 h to obtain pre-oxidized SiC particles.

[0095] Preparation of CNTs / Al precursor:

[0096] The CNTs are pickled and passivated (ultrasonic vibration in hydrochloric acid for 4 h), then solid-liquid separation is carried out, the solid phase is collected, washed and dried to obtain passivated CNTs;

[0097] The passivated CNTs and aluminum powder (300 mesh) are mixed and ball-milled at a mass ratio of 1:12, the ball-to-material ratio is 1:6, and ball-milling is carried out for 2 h to obtain the CNTs / Al precursor.

[0098] Preparation of metal melt:

[0099] The metal raw materials are configured according to the mass percentage content of each metal element component, and after the metal raw materials are mixed, the temperature is raised to 670 °C. After all the metals are melted, it is kept warm for 5 min to obtain the matrix alloy melt;

[0100] The slag on the matrix alloy melt is skimmed off, a refining agent (hexachloroethane, 0.3 wt%) is added, the melt is stirred for 5 min, and slagging is carried out to obtain the refined metal melt.

[0101] S2. Preparation of composite material melt:

[0102] After the pre-oxidized SiC particles, CNTs / Al precursor and refined metal melt are mixed, the melt temperature is reduced to 610 °C, and the melt is mechanically stirred in a semi-solid state for 30 min to obtain the CNTs-SiCp / Al composite material melt.

[0103] S3. Suction casting:

[0104] The melt of CNTs-SiCp / Al composite material is heated to 640 °C, and the vacuum suction casting technology is adopted. The melt is suction cast under the pressure difference formed by the inert gas and the vacuum. A cooling water channel is arranged inside the suction casting mold, and an aluminum matrix composite casting is obtained under the effect of rapid cooling.

[0105] S4. Heat treatment:

[0106] The aluminum matrix composite casting is successively subjected to solution treatment, quenching and aging treatment;

[0107] The solution treatment temperature is 515 °C; the solution treatment time is 5 h;

[0108] The aging treatment temperature is 180 °C; the aging treatment time is 10 h.

[0109] The microstructure of the aluminum matrix composite material in this embodiment is shown in Figure 2 , and the results show that the reinforcing phase is uniformly dispersed in the matrix alloy, and the pinning effect of the grain boundary by the reinforcing phase is obvious.

[0110] The tensile strength of this composite material reaches 461 MPa at room temperature (25 °C); at a high temperature of 300 °C, the tensile strength reaches 185 MPa.

[0111] Example 2

[0112] This embodiment is an aluminum matrix composite material, which is composed of a matrix alloy and a reinforcing phase.

[0113] The aluminum matrix composite material in this embodiment is composed of the following components by mass percentage:

[0114] The aluminum matrix composite material in this embodiment is composed of the following components by mass percentage:

[0115] Si 4%, Cu 1.5%, Mg 0.3%, Ag 0.1%, Mn 0.2%, Ti 0.1%, Zr 0.1%, SiC particles (12 μm) 10%, carbon nanotubes 1.3% and the balance Al.

[0116] The preparation method of the aluminum matrix composite material in this embodiment consists of the following steps:

[0117] S1. Raw material preparation:

[0118] High-temperature pre-oxidation treatment of SiC particles:

[0119] The SiC particles (D50 is 12 μm) are oxidized at 1100 °C for 4 h in an oxygen atmosphere to obtain pre-oxidized SiC particles.

[0120] Preparation of CNTs / Al precursor:

[0121] After subjecting CNTs to pickling passivation treatment (ultrasonic vibration in hydrochloric acid for 4 h), solid-liquid separation was carried out, the solid phase was collected, washed and dried to obtain passivated CNTs;

[0122] The passivated CNTs and aluminum powder (300 mesh) were mixed and ball-milled at a mass ratio of 1:9, the ball-to-material ratio was 1:6, and ball-milling was carried out for 2 h to obtain a CNTs / Al precursor.

[0123] Prepare the molten metal:

[0124] According to the mass percentage content of each metal element component, the metal raw materials were configured, and after mixing the metal raw materials, the temperature was raised to 650 °C. After all the metals were melted, it was kept warm for 5 min to obtain a matrix alloy melt;

[0125] The slag on the matrix alloy melt was skimmed off, a refining agent (hexachloroethane, 0.3 wt%) was added, the melt was stirred for 5 min, and slag removal was carried out to obtain a refined molten metal.

[0126] S2. Prepare the composite material melt:

[0127] After mixing the pre-oxidized SiC particles, CNTs / Al precursor and the refined molten metal, the temperature of the melt was lowered to 620 °C, and the melt was mechanically stirred in a semi-solid state for 20 min to obtain a CNTs-SiCp / Al composite material melt.

[0128] S3. Suction casting:

[0129] The temperature of the CNTs-SiCp / Al composite material melt was raised to 650 °C, and vacuum suction casting technology was adopted. The melt was suction-cast under the pressure difference formed by inert gas and vacuum. A cooling water channel was provided inside the suction casting mold, and an aluminum matrix composite material casting was obtained under the effect of rapid cooling.

[0130] S4. Heat treatment:

[0131] The aluminum matrix composite material casting was successively subjected to solution treatment, quenching and aging treatment;

[0132] The solution treatment temperature was 515 °C; the solution treatment time was 5 h;

[0133] The aging treatment temperature was 180 °C; the aging treatment time was 10 h.

[0134] In this embodiment, the microstructure of the aluminum matrix composite material is shown in Figure 3 , and the results show that the reinforcing phase is uniformly dispersed in the matrix alloy, and the pinning effect of the grain boundaries by the reinforcing phase is obvious.

[0135] The tensile strength of this composite material reaches 452 MPa at room temperature (25 °C); at a high temperature of 300 °C, the tensile strength reaches 190 MPa.

[0136] In this embodiment, a high-modulus heat-resistant CNTs-SiCp hybrid reinforced aluminum matrix composite is obtained according to the above ratio. Figure 3 The microstructure of the material is shown as follows. The results show that the reinforcing phases are uniformly dispersed in the matrix alloy, and the pinning effect of the grain boundaries by the reinforcing phases is obvious. The hardness of the material is measured to be 186 HBw.

[0137] Figure 4 The worn surface morphology of the material after the dry sliding friction and wear test under high pressure is shown as follows. It can be seen that only slight scratching deformation occurs on the material, the width of the plowed groove formed becomes smaller, it is smooth and flat along the sliding direction, and the wear resistance of the material is excellent.

[0138] Comparative Example 1

[0139] This comparative example is an aluminum matrix composite. The difference from Example 1 is that the SiC particles are not pre-oxidized.

[0140] The results of this example show that severe agglomeration of SiCp occurs, the tissue performance uniformity is poor, the tensile strength at room temperature (25 °C) is 269 MPa; at a high temperature of 300 °C, the tensile strength is 74 MPa.

[0141] Comparative Example 2

[0142] This comparative example is an aluminum matrix composite. The difference from Example 1 is that the CNTs are added as passivated CNTs; that is, the CNTs are not ball-milled after being mixed with aluminum powder and are not added in the form of CNTs / Al precursor.

[0143] The results of this example show that the matrix structure is coarse, the reinforcing phases segregate severely at the grain boundaries, the tensile strength at room temperature (25 °C) is 329 MPa; at a high temperature of 300 °C, the tensile strength is 125 MPa.

[0144] Comparative Example 3

[0145] This comparative example is an aluminum matrix composite. The difference from Example 1 is that no CNTs are added.

[0146] The results of this comparative example show that the tensile strength at room temperature (25 °C) is 312 MPa; at a high temperature of 300 °C, the tensile strength is 118 MPa.

[0147] The test results of the mechanical properties of the aluminum matrix composites in the examples and comparative examples of this application are shown in Table 1.

[0148] .

[0149] In the embodiments of the present application, a high-modulus heat-resistant CNTs-SiCp hybrid reinforced aluminum matrix composite material is obtained according to the above ratio. The reinforcing phase is uniformly dispersed in the matrix alloy, and the pinning effect of the grain boundaries by the reinforcing phase is obvious. The mechanical properties of the heat-treated material are detected. The tensile strength of the composite material reaches more than 450 MPa at room temperature; at a high temperature of 300 °C, the tensile strength is stably maintained at more than 180 MPa.

[0150] It should be noted that the present application is not limited to the above embodiments. The above embodiments are only examples, and embodiments with the same structure and the same function and effect as the technical idea within the scope of the technical solution of the present application are included in the technical scope of the present application. In addition, within the scope of not departing from the gist of the present application, various deformations that can be conceived by those skilled in the art are applied to the embodiments, and other ways constructed by combining some constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An aluminum matrix composite material, characterized in that, Composed of components in the following mass percentages: Si 4.0% - 10%, Cu 1.5% - 6.5%, Mg 0.3% - 1.0%, Ag 0.1% - 0.6%, Mn 0.02% - 0.3%, Ti 0.02% - 0.5%, Zr 0.01% - 0.2%, micron-sized SiC particles 5% - 30%, carbon nanotubes 0.1% - 3%, and the balance is Al; The preparation method of the aluminum matrix composite material includes the following steps: Subject the SiC particles to high-temperature pre-oxidation treatment to obtain pre-oxidized SiC particles; Ball-mill aluminum powder and carbon nanotubes to obtain a carbon nanotube / Al precursor; Mix the metal melt, pre-oxidized SiC particles and the carbon nanotube / Al precursor and then perform suction casting. After suction casting, perform heat treatment to obtain the aluminum matrix composite material; The temperature of the high-temperature pre-oxidation treatment is 800°C - 1200°C; The mass ratio of the aluminum powder to the carbon nanotubes is 10 - 20:

1.

2. The aluminum matrix composite material according to claim 1, characterized in that, The particle size of the micron-sized SiC particles is 3μm - 15μm; And / or, the mass fraction of the micron-sized SiC particles is 10% - 30%; And / or, the mass fraction of the carbon nanotubes is 0.3% - 2%; And / or, the aspect ratio of the carbon nanotubes is 50 - 200:

1.

3. The aluminum matrix composite material according to claim 2, characterized in that The particle size of the micron-sized SiC particles is 5μm - 15μm.

4. The aluminum matrix composite material according to claim 1, characterized in that, The hardness of the aluminum matrix composite material is above 180 HBW; And / or, the tensile strength of the aluminum matrix composite material at 300°C is above 180 MPa; And / or, the tensile strength of the aluminum matrix composite material at 25°C is above 450 MPa.

5. Application of an aluminum matrix composite material according to any one of claims 1 to 4 in the preparation of high-temperature wear-resistant parts.

6. A method for preparing an aluminum matrix composite material, characterized in that Including the following steps: Subject the SiC particles to high-temperature pre-oxidation treatment to obtain pre-oxidized SiC particles; Ball-mill aluminum powder and carbon nanotubes to obtain a carbon nanotube / Al precursor; Mix the metal melt, pre-oxidized SiC particles and the carbon nanotube / Al precursor and then perform suction casting. After suction casting, perform heat treatment to obtain the aluminum matrix composite material; The aluminum matrix composite material is composed of components in the following mass percentages: Si 4.0% - 10%, Cu 1.5% - 6.5%, Mg 0.3% - 1.0%, Ag 0.1% - 0.6%, Mn 0.02% - 0.3%, Ti 0.02% - 0.5%, Zr 0.01% - 0.2%, micron-sized SiC particles 10% - 30%, carbon nanotubes 0.3% - 3%, and the balance is Al; The temperature of the high-temperature pre-oxidation treatment is 800°C - 1200°C; The mass ratio of the aluminum powder to the carbon nanotubes is 10 - 20:

1.

7. The preparation method according to claim 6, wherein, The time of the high-temperature pre-oxidation treatment is 3h - 8h; And / or, the particle size of the micron-sized SiC particles is 5μm - 15μm; And / or, the atmosphere of the high-temperature pre-oxidation treatment is an oxygen atmosphere.

8. The preparation method according to claim 6, characterized in that, The ball-to-material ratio of the ball-milling is 1:4 - 8; And / or, the time of the ball-milling is 1h - 4h.

9. The preparation method according to claim 6, characterized in that, Melt the metal element source in the aluminum matrix composite material in a vacuum environment and then perform refining to obtain the metal melt; And / or, the melting temperature is 610°C to 700°C; And / or, after melting, it is held for 5 min to 10 min; And / or, the mixing temperature is 600°C to 650°C; And / or, the mixing time is 15 min to 30 min.

10. The preparation method according to claim 6, wherein Before suction casting, vacuum strong shear stirring is applied in the semi-solid range; And / or, the suction casting is vacuum suction casting; And / or, the temperature of the suction casting is 20°C to 50°C above the liquidus; 11. The preparation method according to claim 6, characterized in that, The heat treatment includes solution treatment, quenching and aging treatment; And / or, the temperature of the solution treatment is 500°C to 530°C; the time of the solution treatment is 2 h to 10 h; And / or, the temperature of the aging treatment is 180°C to 220°C; the time of the aging treatment is 6 h to 15 h.

12. Application of an aluminum matrix composite material prepared by the preparation method according to any one of claims 6 to 11 in the preparation of high-temperature wear-resistant parts.

Citation Information

Patent Citations

  • Squeeze casting Al-Si-Cu alloy material

    CN101376937A

  • Nano-carbon-reinforced wear-resistant composite material

    CN105483420A

  • Preparation method of carbon nanotube strengthened aluminum-based composite material

    CN105734322A

  • Al / SiC composite material and preparation method thereof

    CN115637346A